A tale of two cities (and one vowel): Sociolinguistic variation in Swedish. (17th June 2016) - Gross, Johan; Boyd, Sally; Leinonen, Therese; Walker, James A.
Abstract: Previous studies of language contact in multilingual urban neighborhoods in Europe claim the emergence of new varieties spoken by immigrant-background youth. This paper examines the sociolinguistic conditioning of variation in allophones of Swedish /ε:/ of young people of immigrant and nonimmigrant background in Stockholm and Gothenburg. Although speaker background and sex condition the variation, their effects differ in each city. In Stockholm there are no significant social differences and the allophonic difference appears to have been neutralized. Gothenburg speakers are divided into three groups, based on speaker origin and sex, each of which orients toward different norms. Our conclusions appeal to dialectal diffusion and the desire to mark ethnic identity in a diverse sociolinguistic context. These results demonstrate that not only language contact but also dialect change should be considered together when investigating language variation in modern-day cities.